66 Bone health in gynaecological oncology: a survey of tertiary care clinicians' attitudes and practices in the prevention and management of cancer treatment-induced bone loss. (13th November 2020) - O'Gorman, C; Gleeson, N
Abstract : Introduction: Women with gynaecological cancers are at increased risk of cancer treatment-induced bone loss (CTIBL). Care gaps in CTIBL have been demonstrated in other oncologic settings. This study explores the attitudes and practices of tertiary care clinicians in the prevention and management of CTIBL in the gynaecologic oncology setting. Methods: Online survey of the membership of relevant professional medical body. Results: Tertiary care clinicians appreciate the importance of attention to bone health in women with gynaecological cancers. Clinical practice and opinions on which healthcare professional should provide this care vary significantly, with over one third of respondents of the opinion that it does not fall within the remit of their care. Rates of referral for quantitative bone density assessment, optimisation of calcium and vitamin D levels, and familiarity with standard risk fracture scoring systems were low. Conclusion/Implications: This is the first study to examine the attitudes and practices of tertiary carers of women with gynaecological cancers in relation to CTIBL. Opinions on responsibility for attention to bone health vary widely. Perception of bone health as low priority has been demonstrated among general practitioners so provision of bone health care in the community should not be assumed. Robust guidance on the prevention and treatment of osteoporosis in gynaecologic oncology and impeccable communication with other healthcare providers is paramount. Many women are living years with and beyond gynaecological cancer and so our focus must shift from survivorship alone to quality of health and all aspects of well woman care.